Imperative sentence found in Call of Duty Modern Warfare Campaign - Kevin Stephanus; Ni Made Verayanti Utami; Putu Devi Maharani (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This study entitled An Analysis of Types of Imperative Sentence Found in Call of Duty Modern Warfare Campaign. This research aims to find out the types of imperative sentence Call of Duty Modern Warfare Campaign. The theory used in this research is theory proposed by Quirk et. al. (1985) in their book entitled A Comprehensive of English Language about types of imperative sentence which consist five types of imperative sentence in this research, there are Imperative without subject, imperative with subject, imperative with let, Negative imperative and imperative with do and to determine the constituent structure by using tree diagram based on the theory proposed by Brown and Miller (1991). The data were collected through documentation method by playing and record the game, note taking and classifying the data based on imperative sentence. The analysis of the data was conducted qualitative method and presented decrepitly. The method that applied in presenting the result of the analysis were used formal and informal method. The analysis of the data was conducted qualitative method and presented decrepitly.